Ambient air pollution is associated with vascular disease in Ugandan HIV-positive adolescents. (1st May 2022) - Toe, Sophia; Nagy, Matthew; Albar, Zainab; Yu, Jiao; Sattar, Abdus; Nazzinda, Rashida; Musiime, Victor; Etajak, Samuel; Walyawula, Felix; McComsey, Grace A.; Atuyambe, Lynn M.; Dirajlal-Fargo, Sahera
Abstract : Objective: In this study, we aim to investigate the relationship between particulate matter, a common proxy indicator for air pollution, and markers of inflammation, monocyte activation, and subclinical vascular disease. Design: A cross-sectional study. Methods: Adolescents with perinatally acquired HIV (PHIV) and HIV-uninfected adolescents between 10 and 18years living near Kampala, Uganda were included. Daily ambient concentrations of particulate matter (PM2.5 ) were measured from the Eastern Arica GEOHealth Hub. Outcome variables measured were carotid intima-media thickness (IMT), as well as plasma markers of systemic inflammation, oxidized lipids, and gut integrity. Multivariable quantile regression models were used to explore the relationship between PM2.5 and IMT. Results: One hundred and nineteen participants (69 PHIV, 50 HIV-uninfected) were included. The median (Q1, Q3) age was 12.7 (11.4, 14.2) years, 55% were girls. Median daily PM2.5 exposure was 29.08 μg/m 3 (23.40, 41.70). There was no significant difference in exposure of PM2.5 between groups (P   =  0.073). PM2.5 significantly correlated with intestinal permeability (zonulin; r  = 0.43, P  < 0.001), monocyte activation (soluble CD163: r   =  0.25, P  = 0.053), and IMT (r   =  0.35, P  = 0.004) in PHIV but not in HIV-uninfected ( P  ≥ 0.05). In multivariable quantile regression, after adjusting for age, sex, poverty level, soluble CD163, and zonulin, daily PM2.5 concentrations remained associated with IMT [ β   =  0.005, 95% CI (0.0003–0.010), P  = 0.037] in adolescents with PHIV. Conclusion: Adolescents in urban Uganda are exposed to high levels of air pollution. Both PM2.5 and HIV have independently been observed to contribute to atherosclerotic disease, and our findings suggest the combined effects of HIV and air pollution may amplify the development of cardiovascular disease.